AGROCHEMICAL PROPERTIES AND FERTILITY OF LIGHT-COLORED GRAY SOILS OF SOUTHERN FERGANA (Scientific journal of the Fergana State University, 2026)
According to the results obtained from research conducted on irrigated light gray soils of the Southern Fergana region, the agrochemical properties and fertility status of these soils fall within the medium range. The humus content decreases progressively along the soil profile, from approximately 1.3% in the plow layer to about 0.3% in the lower horizons. A similar pattern is observed for total nitrogen: its concentration declines from around 0.11% at the surface to 0.02–0.07% in deeper layers. Total phosphorus remains relatively stable within the range of 0.19–0.20%, while potassium content gradually decreases from 2.2% to about 1.6% with depth.These indicators confirm that the supply of humus and essential nutrients in the soil is at a moderate level. The study also examined changes occurring under the influence of agricultural practices. Based on the findings, scientifically grounded recommendations were developed, including regular application of organic fertilizers to maintain and increase humus reserves, proper management of nutrient balance through agrochemical analyses, and the use of modern irrigation technologies. The implementation of these measures contributes to the long-term preservation of soil fertility and to increased crop productivity.